ChemInform Abstract: Modular CeCl3·7H2O‐Catalyzed Multi‐Component Synthesis of 1, 2, 3, 4‐Tetrasubstituted Pyrroles under Microwave Irradiation and Their Further Trichloroisocyanuric Acid‐Mediated Conversion into 5‐Sulfenylpyrrole Derivatives. Issue 9 (4th March 2014) - Silveira, Claudio C.; Mendes, Samuel R.; Martins, Guilherme M.; Schloesser, Sheila C.; Kaufman, Teodoro S.
Abstract A multicomponent synthesis of 1, 2, 3, 4‐tetrasubstituted pyrroles promoted by cerous chloride is carried out under microwave irradiation.